„Muzeum etnograficzne na rozdrożu” Czwarte wiosenne seminarium muzeologiczne - Nadolska-Styczyńska, Anna (Zbiór Wiadomości do Antropologii Muzealnej, 2024)
In previous years, the Department of Ethnology of the Nicolaus Copernicus University, the Faculty of Theology of the University of Warsaw and the Missionary Seminary of the Verbist Fathers in Pieniężno organized a series of meetings under the common title "Spring Museological Seminars". Until 2019, we met three times, and reports from the conference and some texts of the speeches were published in ZWAM. In 2024, the Fourth Spring Museological Seminar was held (May 13–15), entitled: The Ethnographic Museum at the Crossroads, which this time took as its main topic the role and position of the contemporary ethnographic museum. The organizers of this year’s meeting were: the Polish Ethnological Society, Branch in Łódź and the Missionary House of St. Stanisław Kostka in Chludowo, as well as the Editorial Office of the magazine ZWAM in cooperation with the Museological Section of the Polish Ethnological Society and the Department of Ethnology and Cultural Anthropology of the Nicolaus Copernicus University in Toruń. This time we met at the Mission House of St. Stanisław Kostka in Chludowo (SVD) near Poznań. The text presents the nature of this meeting and is also an introduction to selected articles resulting from the workshops.